Proposed Business Strategy for Hotel Grandhika Iskandarsyah Jakarta (PT Adhi Commuter Properti) - Tria Fakhrozi, Randy (Journal of Economics and Business UBS, 2025)
This study aims to determine the influence of leadership style and employee welfare on work productivity at PT. Hayyu Pratama East Kalimantan. The background of this research is based on indications of a decrease in employee productivity which is allegedly influenced by low motivation and job satisfaction. The research method used is quantitative with a descriptive approach. Data were collected through questionnaires of 48 respondents and analyzed using multiple linear regression. The test results partially showed that the leadership style and employee welfare had no significant effect on productivity. However, the results of the simultaneous test showed that together these two variables had a significant effect on employee productivity. This study concludes that a holistic approach to human resource management is needed, where leadership styles and employee welfare complement each other in driving workforce productivity. This research offers practical implications for hotel management in strategic planning and serves as a valuable reference for other hospitality businesses navigating competitive and dynamic markets.